Analisis Kemampuan Membuat Keramik Oleh Siswa Kriya Keramik SMK Negeri 2 Sukawati - Pande Putu Sastra Anda Anindia; I Wayan Suardana; I Gst. Ngurah Agung Jaya CK (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
Teaching Assistance in the Independent Learning-Independent Campus (MBKM) program has a goal, to be able to carry out sharing activities in the field of knowledge in educational units. This study aims to analyze the ability to make ceramics by class XI students majoring in Ceramic Crafts at SMK Negeri 2 Sukawati. The problem focuses on 2 aspects, namely: 1) the ability to make ceramics for class XI students in terms of the intellectual aspect of ideas, and 2) the ability to make ceramics for class XI students in terms of technical mastery. Based on the results of research on the ceramic works of class XI students majoring in Ceramic Crafts, there is still a need for much improvement. Of the 5 samples studied, only a few got good marks, and the rest got sufficient marks, from the intellectual/idea aspect 4 works got good marks, and 1 work got good marks. enough, while from the aspect of technical mastery, 3 works got good marks, 1 work got very good marks, and 1 work got enough marks.